LEGAL CHALLENGES OF REDUCTION OF THE TAX BURDEN ON LABOUR IN THE REPUBLIC OF CROATIA (EU and comparative law issues and challenges series (ECLIC), 2019)
Factor of labour has major role in the functioning of the economy. When it comes to employees, the remuneration they receive for their work, usually called pay or income, is in principle their main source of income and therefore has a great impact on their ability to spend and / or save. The paper analyzes the effect of changes in tax rates in the system of mandatory social contributions and personal income tax on tax burden on labour in Croatia. When it comes to the tax burden on labour, it is about taxation of the gross income of natural persons. The gross income of natural persons in Croatia is taxed with several tax forms: employer and employee mandatory social contributions, personal income tax and surtax to personal income tax. Changes in tax rates and other tax elements (eg personal deduction, tax brackets) are subject to frequent changes in order to achieve certain goals of economic and fiscal policy. EUROSTAT data show that Croatia is in the top five EU countries when it comes to tax burden on labour. Measures of tax policy and numerous tax reforms have tried to correct this fact. The main objective of this paper is to review the effects of such changes on the overall tax burden, the tax burden distribution and progressiveness and the level of tax revenues (fiscal impact). We consider it important to note that the framework of this paper does not allow a detailed analysis and that we are forced to limit ourselves exclusively to some aspects of the issue at hand.